PENINGKATAN AKTIVITAS DAN HASIL BELAJAR IPA PESERTA DIDIK MELALUI PENERAPAN KETERAMPILAN PROSES SAINS PADA MATERI SISTEM PERNAPASAN KELAS VIII SMP NEGERI 1 POLONGBANGKENG UTARA KABUPATEN TAKALAR - Nadya Nurul Isnaeni; Narhayati B; Andi Faridah Arsal (Media Agribisnis, 2019)
This research is classroom action research which aims to improve the learning process so as to increase the activity and learning outcomes of learners’ throng- application of Science Process Skills on the material of the VIII class breathing system in SMP Negeri 1 Polongbangkeng Utara. The study was conducted in 2 cycles starting from planning, implementation of the action, evaluation, until the reflection cycle II. The subject of the research is the students of class VIII2 SMP Negeri 1 Polongbangkeng Utara. Data collection was conducted in the even semester of e academic year 2017/2018. Research data collected there are two activities and learning outcomes of learners. Student learning activities are collected during the; learning process which is observed by two observers by using observation sheet, then the learning result data is obtained through the evaluation test which is done at the third meeting at the end of the cycle, the final test of the given cycle is a matter of multiple-choice as much as 20 (twenty) numbers. All data obtained were analyzed in 2 ways, namely qualitative analyses for learners and quantitative learning activities for learners’ learning _ outcomes. The results of the search on learning activities of students showed the average in the first cycle of 7194%; while in the second cycle of 82.49%, so an increase of 10.55% Student learning outcomes also experienced an average increase of 77.83 m the first cycle and the average value of 82.67 in cycle 11. Through quantitative analysis, it is known to the student’s completeness category in which the percentage of learners who completed in the first cycle is 70%, while in cycle II reaches 80%. So, it can be concluded that the application of science process skills can improve the activities and learning outcomes of learners. Keywords: Process skill science, the student’s activity, the student’s learning outcome